2021
DOI: 10.3389/fpsyt.2021.683832
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Literacy Levels of Medical Staff in China: An Assessment Based on a Meta-Analysis

Abstract: Background: The awareness rate of mental health knowledge among medical staff is an important evaluation index to assess the service capacity of a country or region, and this indicator in China has not been quantitatively evaluated.Study Design: This study systematically combined pertinent quantitative study data from previous related studies to conclude the awareness rate of mental health knowledge among Chinese medical staff.Methods: Related studies from five electronic databases were searched, and a meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
1
2
Order By: Relevance
“…In this study, we observed that the overall rate of awareness of mental health knowledge among primary care workers in Wuhan, China, was 84.4 %, which is slightly higher than levels that have previously been reported [ 38 ]. This finding might be related to a pilot project of the national social and psychological service system that was implemented in Wuhan.…”
Section: Discussioncontrasting
confidence: 58%
“…In this study, we observed that the overall rate of awareness of mental health knowledge among primary care workers in Wuhan, China, was 84.4 %, which is slightly higher than levels that have previously been reported [ 38 ]. This finding might be related to a pilot project of the national social and psychological service system that was implemented in Wuhan.…”
Section: Discussioncontrasting
confidence: 58%
“…These findings contradict the Aljassim and Ostini review of health literacy in rural and urban populations [20]. According to the above research, significantly higher levels of health literacy were found in urban residents [21][22][23]. It should be noted, however, that the aforementioned studies did not include European countries.…”
Section: Data Is Presented As: An (%) or Bmean (M) ± Standard Deviati...contrasting
confidence: 56%
“…Medical staff also experienced psychological stress from work-related burnout and somatic symptoms ( 10 ). A meta-analysis of the awareness rate of medical staff shows that the highest awareness rate comes from psychological hospital staff, with an awareness rate of 88%; the awareness rate of non-psychiatric medical staff was only 68%, which was lower than general population ( 11 ). Meanwhile, another meta-analysis shows key point studies that conducted in China reported more mental problems than in other countries ( 12 ).…”
Section: Introductionmentioning
confidence: 97%